A Review of Cartilage Defect Treatments Using Chitosan Hydrogels in Experimental Animal Models - Souza-Silva, Lais C.; Cristina Santi Martignago, Cintia; Garcia Motta, Homero; Bonifacio, Mirian; Regina Avanzi, Ingrid; Assis, Lívia; Araki Ribeiro, Daniel; Risso Parisi, Julia; Claudia Rennó, Ana (Current Pharmaceutical Biotechnology, 2024)
Introduction: Chitosan (CS) is a polycationic polysaccharide comprising glucosamine and N-acetylglucosamine and constitutes a potential material for use in cartilage tissue engineering. Moreover, CS hydrogels are able to promote the expression of cartilage matrix components and reduce inflammatory and catabolic mediator production by chondrocytes. Although all the positive outcomes, no review has analyzed the effects of CS hydrogels on cartilage repair in animal models. Methods: This study aimed to review the literature to examine the effects of CS hydrogels on cartilage repair in experimental animal models. The search was done by the descriptors of the Medical Subject Headings (MeSH) defined below: “Chitosan,” “hydrogel,” “cartilage repair,” and “in vivo.” A total of 420 articles were retrieved from the databases Pubmed, Scopus, Embase, Lilacs, and Web of Science. After the eligibility analyses, this review reported 9 different papers from the beginning of 2002 through the middle of 2022. Results: It was found that cartilage repair was improved with the treatment of CS hydrogel, especially the one enriched with cells. In addition, CS hydrogel produced an upregulation of genes and proteins that act in the cartilage repair process, improving the biomechanical properties of gait. Conclusion: In conclusion, CS hydrogels were able to stimulate tissue ingrowth and accelerate the process of cartilage repair in animal studies.
Keywords: tissue engineering